Suppression of Ongoing Experimental Arthritis by a Chinese Herbal Formula (Huo-Luo-Xiao-Ling Dan) Involves Changes in Antigen-Induced Immunological and Biochemical Mediators of Inflammation. (19th October 2010) - Yang, Ying-Hua; Rajaiah, Rajesh; Lee, David Y.-W; Ma, Zhongze; Yu, Hua; Fong, Harry H. S.; Lao, Lixing; Berman, Brian M.; Moudgil, Kamal D.
Abstract : Rheumatoid arthritis (RA) is one of the major autoimmune diseases of global prevalence. The use of the anti-inflammatory drugs for the treatment of RA is associated with severe adverse reactions and toxicity. This limitation has necessitated the search for novel therapeutic products. We report here a traditional Chinese medicine-based herbal formula, Huo luo xiao ling dan (HLXL), which has potent antiarthritic activity as validated in the rat adjuvant-induced arthritis (AA) model. HLXL (2.3 g/Kg) was fed to Lewis (RT.1 1 ) rats daily by gavage beginning at the onset of arthritis and then continued through the observation period. HLXL inhibited the severity of ongoing AA. This suppression of arthritis was associated with significant alterations in the T cell proliferative and cytokine responses as well as the antibody response against the disease-related antigen, mycobacterial heat-shock protein 65 (Bhsp65). There was a reduction in the level of the proinflammatory cytokines IL-17 and IL-1β but enhancement of the anti-inflammatory cytokine IL-10 level. In addition, there was inhibition of both the anti-Bhsp65 antibody response and the serum level of nitric oxide. Thus, HLXL is a promising CAM modality for further testing in RA patients.